Effectiveness of Snakes Ladders and Leaflet n Teenagers’ Knowledge and Attitude About Stunting Prevention - Putri Barkun; Wahyuningsih Wahyuningsih; Slamet Budiyanto (Yayasan Adra Karima Hubbi, 2024)
Stunting prevention must start as early as possible. Teenagers are expected to have a healthy lifestyle, and good nutrition and avoid early marriage. This is done to prevent giving birth to stunted children. This research aims to determine the effectiveness of snakes and ladders media and leaflets in preventing stunting at SMKN 01 Warungasem. The research method used is quasi-experimental with pre and post-design. With a population of 119 students. The sample used was purposive sampling. By collecting data through questionnaire interviews. Data analysis uses the Paired T-test. Results of statistical tests using the Paired T-test showed that the use of snakes and ladders educational media for knowledge resulted in a P value of 0.0001, while for attitudes a P value of 0.0001 was obtained. For leaflet media, the knowledge variable has a P value of 0.0001, while for attitude it has a P value of 0.0001. For the N Gain Score analysis, the Snakes and Ladders media effectiveness score results is in 64,43 % (enough) effective, while the effectiveness score results in increasing attitudes are 51,91% (less) effective, effectiveness score results using leaflet media is in the 54,98 % (less) effective, and media effectiveness score results for attitude is not effective 23,92. From the results above, it can be concluded that there is a difference in the average knowledge and attitude of using leaflets and snakes and ladders media as well as Snakes and Ladders media for Stunting Prevention which is proven to be more effective in increasing the knowledge and attitudes of teenagers. The recommendation given is the need for a comprehensive approach to education carried out by utilizing media that can raise the motivation of teenagers to know, want, be able and be independent to prevent stunting.